2007
DOI: 10.1111/j.1532-5415.2007.01125.x
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes of Older Korean Americans Toward Mental Health Services

Abstract: Given the increasing evidence that older ethnic minorities underuse mental health services, the present study assessed determinants of attitudes toward mental health services with a sample of older Korean Americans (N = 472). Adapting Andersen's behavioral health model, predisposing factors (age, sex, marital status, education, length of residence in the United States), mental health needs (anxiety, suicidal ideation, depressive symptoms), and enabling factors (personal experiences and beliefs) were considered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
77
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(88 citation statements)
references
References 22 publications
11
77
0
Order By: Relevance
“…In general, utilization rates for mental health services decrease markedly as people age (Crabb and Hunsley, 2006;Cole et al, 2008). This trend of decreasing mental health service use rates is common and has been noted in several studies throughout other parts of the world, including the United States (Jang et al, 2007;Zuvekas and Fleishman, 2008) and the Netherlands (Cuijpers, 1998;Westerhof et al, 2008). In the elderly, inequities in mental health care, specifically as it pertains to access, acceptability, and appropriateness of care may be more important.…”
Section: Discussionmentioning
confidence: 91%
“…In general, utilization rates for mental health services decrease markedly as people age (Crabb and Hunsley, 2006;Cole et al, 2008). This trend of decreasing mental health service use rates is common and has been noted in several studies throughout other parts of the world, including the United States (Jang et al, 2007;Zuvekas and Fleishman, 2008) and the Netherlands (Cuijpers, 1998;Westerhof et al, 2008). In the elderly, inequities in mental health care, specifically as it pertains to access, acceptability, and appropriateness of care may be more important.…”
Section: Discussionmentioning
confidence: 91%
“…Studies have suggested that multiple factors at the patient, clinician, and system levels could simultaneously increase outpatient service use among older people with depression and CMI. Unawareness of being depressed or the stigma of pursuing screening or treatment for mental health problems may result in repeatedly ineffective outpatient visits that focus only on chronic medical conditions (Murray et al, 2006;Jang et al, 2007). Poor self-care coupled with lower social support and clinicians' prioritization of CMI over depressive symptoms may also be risk factors for inappropriate management of the complex conditions of older patients with depressive symptoms (Alexopoulos, 2005;McCabe et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Respondents were paid $10 for their participation. Detailed information about the two projects is available elsewhere [25,26].…”
Section: Participants and Data Collectionmentioning
confidence: 99%